HESPERETIN DERIVATIVES AS PPAR γ AGONIST: A PHARMACOPHORE APPROACH - MUTHIAH, RAMANATHAN; CHINNIAH, VIJAYALAKSHMI; ENGELS. S. E., MAIDA (International Journal of Applied Pharmaceutics, 2024)
Objective: The study focuses on enhancing the pharmacological activity of hesperetin, a bioflavonoid, to develop novel derivatives with improved efficacy and reduced side effects compared to existing Thiazolidinediones (TZDs) as PPAR g agonist. Methods: The Methodology involves various computational approaches, including pharmacophore modelling, molecular docking, Molecular Mechanics with Generalised Born and Surface Area Solvation (MMGBSA), and molecular dynamics simulations. Pharmacophore modelling identifies essential binding features validated by Quantitative Structure-Activity Relationship (QSAR) models. Database screening and docking confirm lead compounds' binding affinity, with MMGBSA aiding lead optimization. Toxicological assessment ensures drug likeness and bioavailability. Molecular dynamics simulations explore protein-ligand complex stability and dynamics, revealing insights into their interactions. Results: The results indicate MOL-297 exhibits improved properties over hesperetin, including ADME properties, solubility, blood-brain barrier permeability, docking score, and binding energy. Molecular dynamics simulations confirm Mol-297-PPAR γ complex stability, with favourable ligand-amino acid interactions. Conclusion: The developed new molecule MOL 297, is a novel Peroxisome Proliferator-Activated Receptor (PPAR) gamma agonists with enhanced pharmacological properties, warranting further experimental validation and drug development.